2021
DOI: 10.1002/nafm.10608
|View full text |Cite
|
Sign up to set email alerts
|

Phylogeography, Population Structure, and Historical Demography of Black Drum in North America

Abstract: The Black Drum Pogonias cromis is an abundant estuarine‐dependent fish that supports recreational and commercial fisheries. We examined the phylogeography and historical demography of the Black Drum along the Atlantic and Gulf of Mexico coasts of the United States using mitochondrial DNA sequences and nuclear DNA microsatellites. Black Drum exhibited high haplotype diversity and low nucleotide diversity across its range. We observed 249 haplotypes that resolved into two haplogroups: haplogroup 1 was most abund… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 122 publications
1
4
0
Order By: Relevance
“…Several nongenetic data points exist that imply the potential for population subdivision of Black Drum in Texas beyond the isolation-by-distance pattern described by Karel et al (1996), and consistent with the spatial heterogeneity observed by Williford et al (2021). For instance, in the Baffin Bay complex (BBC) adjacent to the upper Laguna Madre system (ULM), Simmons and Breuer (1962) described divergent morphology of Black Drum adults, which were darker in coloration and often impaired by physical maladies.…”
supporting
confidence: 80%
See 3 more Smart Citations
“…Several nongenetic data points exist that imply the potential for population subdivision of Black Drum in Texas beyond the isolation-by-distance pattern described by Karel et al (1996), and consistent with the spatial heterogeneity observed by Williford et al (2021). For instance, in the Baffin Bay complex (BBC) adjacent to the upper Laguna Madre system (ULM), Simmons and Breuer (1962) described divergent morphology of Black Drum adults, which were darker in coloration and often impaired by physical maladies.…”
supporting
confidence: 80%
“…Unfortunately, the gap in sample coverage between SAB and ULM makes it impossible to know the population genomic status of Black Drum in Aransas Bay and Corpus Christi Bay, major estuaries which lie in the sampling gap. Nevertheless, these data have added much-needed resolution to the picture of Black Drum genetic structure in Texas and have elicited genomic patterns of heterogeneity at small spatial scales more prominently than those found in previous studies with more limited genetic loci (Karel et al 1996;Williford et al 2021).…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…As well as different life history traits exhibited among P. cromis populations have suggested an adaptation to the high salinity of the environment as occur in the Upper Laguna Madre, a hypersaline estuary in Texas, USA (Bumguardner et al 1996, Olsen et al 2018. Further studies ought to combine information of life history traits of P. courbina in all localities studied which can help to confirm results obtained based on mitochondrial DNA (Williford et al 2021).…”
Section: Phylogenetic Analyses and Divergence Time Estimate Between P...mentioning
confidence: 86%